A survey of phenotype II in familial Mediterranean fever. Issue 11 (1st November 2000) - Melikoğlu, Melike; Özdoğan, Huri; Korkmaz, Cengiz; Kasapçopur, Özgür; Arısoy, Nil; Akkuş, Semra; Fresko, I˙zzet; Yazıcı, Hasan
Abstract : OBJECTIVE: Phenotype II in familial Mediterranean fever (FMF) is the onset of amyloidosis before the onset of FMF with its typical attacks, or as an isolated finding in a member of an FMF family. Its presence was investigated by looking for proteinuria among the asymptomatic relatives of patients with FMF complicated by amyloidosis and among the asymptomatic relatives of patients with juvenile chronic arthritis (JCA) complicated by amyloidosis, used as controls. METHODS: The relatives of the index patients (13 with FMF and amyloidosis) and controls (6 with JCA and amyloidosis) were screened for proteinuria. Rectal biopsies were performed when proteinuria was significant (⩾300 mg/d). RESULTS: 461 relatives were screened in the FMF group and 269 among the controls. Two of the FMF relatives and one JCA relative had no symptoms of FMF but had significant proteinuria. Rectal biopsy for amyloidosis was negative in all instances of significant proteinuria. CONCLUSION: Phenotype II is uncommon among the relatives of patients with FMF and amyloidosis.